2012
DOI: 10.3390/ijerph9114068
|View full text |Cite
|
Sign up to set email alerts
|

Drunk and Disorganised: Relationships between Bar Characteristics and Customer Intoxication in European Drinking Environments

Abstract: Preventing alcohol-related harm in drinking environments is a growing international priority. Factors relating to the physical, social and staffing environments in bars can contribute to increased alcohol consumption and harm. Understanding the relationships between such factors and intoxication in European drinking environments is critical to developing appropriate interventions. We undertook a quantitative observational study in 60 bars in four European cities, in The Netherlands, Slovenia, Spain and the UK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…When the priming dose of alcohol contained caffeine, either as part of an energy drink (Marczinski et al, 2013, in press) or as an additive (Heinz et al, 2013), participants reported a greater desire for more alcohol. These laboratory-based findings coincide with findings from field studies where bar patrons who consume AmED beverages are more likely to leave bars intoxicated (Hughes et al, 2012; Thombs et al, 2010). There appears to be a dose dependent relationship between level of caffeine use (via energy drinks or cola beverages) and the magnitude of alcohol intoxication in bar patrons (Thombs et al, 2011).…”
supporting
confidence: 83%
“…When the priming dose of alcohol contained caffeine, either as part of an energy drink (Marczinski et al, 2013, in press) or as an additive (Heinz et al, 2013), participants reported a greater desire for more alcohol. These laboratory-based findings coincide with findings from field studies where bar patrons who consume AmED beverages are more likely to leave bars intoxicated (Hughes et al, 2012; Thombs et al, 2010). There appears to be a dose dependent relationship between level of caffeine use (via energy drinks or cola beverages) and the magnitude of alcohol intoxication in bar patrons (Thombs et al, 2011).…”
supporting
confidence: 83%
“…This non‐participant observation study identified alcohol‐related affordances related to: alcohol access, regulations, furnishing, alternative opportunities for action, décor and lighting, drink and accessory availability, and action opportunities provided by others. Many of these identified features have been associated with increased, problematic consumption and alcohol‐related harm within previous research (e.g., Doherty & Roche, ; Gruenewald, ; Homel & Clark, ; Hughes et al., , ; Kilfoyle & Bellis, ; Livingston, ; Miller et al., ; Nusbaumer & Reiling, ; Stockwell et al., , ; Toomey et al., ; Wagenaar et al., ). These findings further support the idea that contextual features may influence alcohol consumption, which could help address some of the limitations of dominant social cognition models focusing solely on cognitive determinants of behaviour when looking to prevent alcohol misuse (e.g., Gerrard et al., ; Vlaev & Dolan, ; Webb & Sheeran, ).…”
Section: Discussionmentioning
confidence: 61%
“…The first registration form was based on similar studies in Sweden [35] and new variables were added in 2006. In 2011, the form was based on a schedule developed by Graham et al [38], which Hughes and her colleagues [39] also used.…”
Section: Measurementsmentioning
confidence: 99%